Inhibition of cAMP-Dependent PKA Activates β(2)-Adrenergic Receptor Stimulation of Cytosolic Phospholipase A(2) via Raf-1/MEK/ERK and IP(3)-Dependent Ca(2+) Signaling in Atrial Myocytes - Pabbidi, M. R. (PLoS One, 2016)
We previously reported in atrial myocytes that inhibition of cAMP-dependent protein kinase (PKA) by laminin (LMN)-integrin signaling activates β(2)-adrenergic receptor (β(2)-AR) stimulation of cytosolic phospholipase A(2) (cPLA(2)). The present study sought to determine the signaling mechanisms by which inhibition of PKA activates β(2)-AR stimulation of cPLA(2). We therefore determined the effects of zinterol (0.1 μM; zint-β(2)-AR) to stimulate I(Ca,L) in atrial myocytes in the absence (+PKA) and presence (-PKA) of the PKA inhibitor (1 μM) KT5720 and compared these results with atrial myocytes attached to laminin (+LMN). Inhibition of Raf-1 (10 μM GW5074), phospholipase C (PLC; 0.5 μM edelfosine), PKC (4 μM chelerythrine) or IP(3) receptor (IP(3)R) signaling (2 μM 2-APB) significantly inhibited zint-β(2)-AR stimulation of I(Ca,L) in–PKA but not +PKA myocytes. Western blots showed that zint-β(2)-AR stimulation increased ERK1/2 phosphorylation in–PKA compared to +PKA myocytes. Adenoviral (Adv) expression of dominant negative (dn) -PKCα, dn-Raf-1 or an IP(3) affinity trap, each inhibited zint-β(2)-AR stimulation of I(Ca,L) in + LMN myocytes compared to control +LMN myocytes infected with Adv-βgal. In +LMN myocytes, zint-β(2)-AR stimulation of I(Ca,L) was enhanced by adenoviral overexpression of wild-type cPLA(2) and inhibited by double dn-cPLA(2)(S505A/S515A) mutant compared to control +LMN myocytes infected with Adv-βgal. In–PKA myocytes depletion of intracellular Ca(2+) stores by 5 μM thapsigargin failed to inhibit zint-β(2)-AR stimulation of I(Ca,L) via cPLA(2). However, disruption of caveolae formation by 10 mM methyl-β-cyclodextrin inhibited zint-β(2)-AR stimulation of I(Ca,L) in–PKA myocytes significantly more than in +PKA myocytes. We conclude that inhibition of PKA removes inhibition of Raf-1 and thereby allows β(2)-AR stimulation to act via PKCα/Raf-1/MEK/ERK1/2 and IP(3)-mediated Ca(2+) signaling to stimulate cPLA(2) signaling within caveolae. These findings may be relevant to the remodeling of β-AR signaling in failing and/or aging heart, both of which exhibit decreases in adenylate cyclase activity.